The Effect of Nearpod in Enhancing Writing Skills of Thai EFL Students - Br Samosir, Annida Adhwa; Ginting, Pirman (Universitas Pahlawan Tuanku Tambusai, 2025)
The study was motivated by the identified shortcomings in students’ ability to write effectively in English, the less appealing teaching approach employed by the teachers, the emphasis placed on assignments and tests, and the limited use of interactive learning resources. This study examines how the integration of Nearpod affects the English writing proficiency of students in Satun, Thailand. The objective of this research is to explore how Nearpod influences the improvement of students’ English writing skills in Satun, Thailand. This study employed pretests and posttests as instruments for data collection. This research employs the following data analysis techniques: 1. Normal Distribution Test, 2. Assessment of Variance Homogeneity, and 3. Hypothesis Evaluation Using the t-Test. To test the hypothesis, a t-test was utilized following the assessment of data normality and homogeneity. When the t-test findings indicated a significant impact on fertility (sig (2-tailed) = 0.001 0.05), The rejection of the null hypothesis (Ho) led to the acceptance of the alternative hypothesis (Ha). The utilization of interactive learning media, such as Nearpod, markedly enhances the English ability in written expression Muslim Suka lower secondary school students in Thailand, surpassing the efficacy of conventional teaching approaches.